blue wrote:9r7c4 = [AIC: 3r6c5 = r6c4 - (3=4)r7c4 - (4=9)r8c5] - 9r6c5 = [Kite: 9r6c4 = r6c8 - r5c7 = 9r2c7] => r2c4<>9; stte
Hmmm!!! For some time now, people have abandoned network structures in favor of folding logic into a chain structure. They often use the initial false assumption to bypass writing Kraken Cell logic. I was always leery of these structures, and here's an example why.
What if a basic step existed for -9r7c4 prior to this grid? Then blue's chain would reduce to:
3r6c5 = r6c4 - (3=4)r7c4 - (4=9)r8c5 - 9r6c5 = [Kite: 9r6c4 = r6c8 - r5c7 = 9r2c7] => ???
I don't see this chain reaching a conclusion! Not without including: (3-9)r6c5 = [Kite: 9r6c4 = r6c8 - r5c7 = 9r2c7] to form a forcing chain.
I suspect that blue was trying to circumvent writing the following:
- Code: Select all
Kraken Cell r7c4:
3r7c4 - r6c4 = (3-9)r6c5 \
= [Kite: 9r6c4 = r6c8 - r5c7 = 9r2c7] - 9r2c4
4r7c4 - (4=9)r8c5 - r6c5 /
9r7c4 - 9r2c4
You'll notice that I succumbed to using the Kite instead of its network equivalent. _ _
Crazy Time:
If you were to use the initial false assume "9r7c4 =", then you can turn the above Kraken Cell logic into a wicked (embedded) lasso by:
(a) start with "9r2c4 -" and work your way r-to-l along the lower path to "- 4r7c4"
(b) transition to the upper path using "= 3r7c4"
(c) and then return along the upper path until you reach "- 9r2c4"
Now, that would be an interesting way to fold everything together into a chain structure!!!